An Exploration of the Raya Dunayevskaya Collection – Marxist-Humanism: A Half-Century of its World Development - Eugene Gogol (tripleC: Communication, Capitalism & Critique)
Through an exploration of the Raya Dunayevskaya Collection, major themes of Dunayevskaya’s contribution to Marxist thought and action are presented. Her view of Marx as a philosopher of revolution in permanence, her interpretation of Lenin as a Hegelian-Marxist thinker-activist revolutionary, her reading of Hegel’s Absolutes as New Beginning for our age, her insistence that human subjects of social transformation are not alone muscle but Mind, are revolutionary Reason as well as force, and her efforts to work out and practice a dialectic of organisation and philosophy through the Marxist-Humanist organisation she founded, News and Letters Committees, are briefly discussed using documentation from her archives, which have recently been made available on the Internet.